2017
DOI: 10.3390/ijms18020346
|View full text |Cite
|
Sign up to set email alerts
|

Increased Dicarbonyl Stress as a Novel Mechanism of Multi-Organ Failure in Critical Illness

Abstract: Molecular pathological pathways leading to multi-organ failure in critical illness are progressively being unravelled. However, attempts to modulate these pathways have not yet improved the clinical outcome. Therefore, new targetable mechanisms should be investigated. We hypothesize that increased dicarbonyl stress is such a mechanism. Dicarbonyl stress is the accumulation of dicarbonyl metabolites (i.e., methylglyoxal, glyoxal, and 3-deoxyglucosone) that damages intracellular proteins, modifies extracellular … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
6
0
2

Year Published

2018
2018
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 10 publications
(8 citation statements)
references
References 52 publications
(118 reference statements)
0
6
0
2
Order By: Relevance
“…Due to these insufficient amounts of glutathione, the authors had suggested that TamR cells were more sensitive to dicarbonyl stress. Dicarbonyl stress can result in damage to intracellular proteins, mitochondrial dysfunction and oxidative stress, which eventually leads to cell death [ 51 , 52 ].…”
Section: Resultsmentioning
confidence: 99%
“…Due to these insufficient amounts of glutathione, the authors had suggested that TamR cells were more sensitive to dicarbonyl stress. Dicarbonyl stress can result in damage to intracellular proteins, mitochondrial dysfunction and oxidative stress, which eventually leads to cell death [ 51 , 52 ].…”
Section: Resultsmentioning
confidence: 99%
“…Experimental data have shown that dicarbonyl stress contributes to the impairment of both micro- and macro-vascular dysfunction, also independently of hyperglycemia [12].…”
Section: Dicarbonyl Stress In Aging-related Diseasesmentioning
confidence: 99%
“…Most glycation reactions of MGO occur in the unhydrated form [11], and this probably accounts for its short half-life. The percentage of MGO in its unhydrated form is hundreds of times higher than GO [12], which makes MGO the most reactive dicarbonyl.…”
Section: Introduction—dicarbonyl Stress and Glycationmentioning
confidence: 99%
“…В свою очередь, измененные протеины активируют клетки сосудистого эндотелия, мезангиальные клетки и макрофаги, продуцирующие активные формы кислорода. Таким образом, дикарбонильные соединения принимают участие в формировании механизмов окислительного стресса [7,8,10].…”
Section: результатыunclassified
“…Эти вещества обладают значительной цитотоксичностью, повреждая протеины и нарушая процессы тканевого дыхания, инициируют воспаление. Неблагоприятное интегративное действие на организм химических соединений, несущих в себе пару карбонильных групп, в ситуациях, характеризующихся их усиленной продукцией и нарушением инактивации, получило название «дикарбонильный стресс» [7][8][9].…”
Section: Introductionunclassified